Artificial Intelligence: Legal Status Determination - Velykanova, Maryna; Korchak, Nataliia; Klepikova, Olga; Kibets-Pashutina, Daria; Shyrokova-Murarash, Olga (Law, State and Telecommunications Review, 2022)
[Purpose] To study the feasibility of establishing the status of artificial intelligence and outlining its characteristics, as well as to identify problems associated with the introduction of the subject of legal relations “electronic person”. [Methodology] The main method, used in this article, was analysis of the approaches to understanding the essence of artificial intelligence and concepts of legal personality of the electronic person. [Findings] Based on the analysis of the approaches to understanding the essence of artificial intelligence and concepts of legal personality of the electronic person, the conclusion is that the legal personality of the electronic person depends on the presence of features that characterize it as a subject of law: autonomy (separation) and personalization. [Practical Implications] The practical significance lies in the formation of proposals for improving approaches to establishing the essence of artificial intelligence and determining the legal status of the electronic person.